Detection of glutathione in dairy products based on surface-enhanced infrared absorption spectroscopy of silver nanoparticles - Qi, Wenliang; Tian, Yanlong; Lu, Daoli; Chen, Bin (Frontiers in Nutrition, 2022)
In this paper, silver nanoparticles (AgNPs) were prepared as enhanced substrates for the detection of glutathione in dairy products by polyol reduction of silver nitrate. The infrared spectra were collected and analyzed by surface-enhanced infrared absorption spectroscopy (SEIRA) method of transmission mode using a cell of calcium fluoride window sheet immobilization solution for the study. The disappearance of the thiol (–SH) absorption peak in the infrared spectrum, and the shift of its characteristic absorption peak when glutathione was bound to AgNPs solvate indicated the Ag–S bond interaction and the aggregation of AgNPS. AgNPs accumulate to form “hot spots”, resulting in enhanced electromagnetic fields and thus enhanced infrared signals of glutathione. The intensity of the characteristic absorption peak at 1,654 cm−1 (carbonyl C=O bond stretching) was used for the quantitative analysis of glutathione. After optimizing the conditions, glutathione content in pretreated pure milk and pure ewe's milk was determined using AgNPs in combination with SEIRA. Good linearity was obtained in the range of 0.02–0.12 mg/mL with correlation coefficients (R2) of 0.9879 and 0.9833, respectively, and LOD of 0.02 mg/mL with average spiked recoveries of 101.3 and 92.5%, respectively. The results show that the method can be used for accurate determination of glutathione content in common dairy products.